Beyond Tympanomastoidectomy: A Review of Less Common Postoperative Temporal Bone CT Findings - Panda, A.; Carlson, M.L.; Diehn, F.E.; Lane, J.I. (American Journal of Neuroradiology, 2021)
SUMMARY: Postoperative temporal bone imaging after surgical procedures such as ossiculoplasty, tympanomastoidectomy, cochlear implantation, and vestibular schwannoma resection is often encountered in clinical neuroradiology practice. Less common otologic procedures can present diagnostic dilemmas, particularly if access to prior operative reports is not possible. Lack of familiarity with the less common surgical procedures and expected postoperative changes may render radiologic interpretation challenging. This review illustrates key imaging findings after surgery for Ménière disease, superior semicircular canal dehiscence, temporal encephalocele repairs, internal auditory canal decompression, active middle ear implants, jugular bulb and sigmoid sinus dehiscence repair, and petrous apicectomy.AMEIactive middle ear acoustic implantsELSendolymphatic sacLSClateral semicircular canalMCFmiddle cranial fossaPSCposterior semicircular canalSSCsuperior semicircular canalSSCDsuperior semicircular canal dehiscence